Variations in dissolved organic nitrogen concentration in biofilters with different media during drinking water treatment. (November 2015) - Zhang, Huining; Zhang, Kefeng; Jin, Huixia; Gu, Li; Yu, Xin
Highlights: Dissolved organic nitrogen (DON) concentration varies in water biofiltering. Along the depth of biofilters, DON concentration first decreased and then increased. The greatest variation in DON occurred in the activated carbon biofilter. The physical properties of the biofilter media affected the microbial population. The heterotrophic bacterial proportion may be responsible for DON variation. Abstract: Dissolved organic nitrogen (DON) is potential precursor of disinfection byproducts (DBPs), especially nitrogenous DBPs. In this study, we investigated the impact of biofilters on DON concentration changes in a drinking water plant. A small pilot plant was constructed next to a sedimentation tank in a drinking water plant and included activated carbon, quartz sand, anthracite, and ceramsite biofilters. As the biofilter layer depth increased, the DON concentration first decreased and then increased, and the variation in DON concentration differed among the biofilters. In the activated carbon biofilter, the DON concentration was reduced by the largest amount in the first part of the column and increased by the largest amount in the second part of the column. The biomass in the activated carbon filter was less than that in the quartz sand filter in the upper column. The heterotrophic bacterial proportion among bacterial flora in the activated carbon biofilter was the largest, which might be due to the significant reduction in DON in the first part of the column. Overall, the results indicate that the DON concentration in biofiltered water can be controlled via the selection of appropriate biofilter media. We propose that a two-layer biofilter with activated carbon in the upper layer and another media type in the lower layer could best reduce the DON concentration.